Effect of boric acid content on the properties of magnesium phosphate cement. (30th July 2019) - Ribeiro, D.V.; Paula, G.R.; Morelli, M.R.
Highlights: Effect of boric acid (BA) content on the properties of magnesium phosphate cement was evaluated. Specimens were molded with different BA contents using MgO calcined at 900 and 1110 °C. Effect of the BA concentration on the properties of MPC was evaluated. It was observed an increase in the setting time and a decrease of the porosity of MPC. Abstract: Magnesium phosphate cements (MPC) are materials prepared by reacting magnesium oxide with water-soluble phosphates such as mono-ammonium dihydrogen phosphate (ADP), which solidify at ambient temperature through the formation of hydrated phases in the material. A great advantage of these ceramics is that they acquire mechanical strength at room temperature, which is generally observed only for sintered ceramics. However, owing to the nature of the formation of these cements, hardening (setting) occurs very quickly, and the use of retardants is generally necessary. The effects of the concentration of boric acid, which is used as a retardant additive, on the properties of these materials, such as the formation of phases (analyzed via XRD), setting time, and pore size distribution were evaluated. It was noted that MgO calcined at 1100 °C/2 h had a lower solubility than that of MgO calcined at 900 °C/2 h and that for samples with a high MgO/NH3 H2 PO4 ratio, the increase in retardant concentration did not generate significant changes in the concentration of the hydrated phases formed and for samples with a low MgO/NH3 H2 PO4 ratio, the increase in retardant concentration favored the formation of more of the struvite phase and the disappearance of the dittmarite phase. Additionally, it was found that the traditional setting retardation mechanism proposed in the literature is valid only when there is no excess of retarders in the system.